2021
DOI: 10.1001/jamapediatrics.2021.2025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Symptoms and RNA Levels in Children and Adults With SARS-CoV-2 Infection in the Community Setting

Abstract: IMPORTANCEThe association between COVID-19 symptoms and SARS-CoV-2 viral levels in children living in the community is not well understood. OBJECTIVE To characterize symptoms of pediatric COVID-19 in the community and analyze the association between symptoms and SARS-CoV-2 RNA levels, as approximated by cycle threshold (Ct) values, in children and adults. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used a respiratory virus surveillance platform in persons of all ages to detect community COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 52 publications
(112 reference statements)
12
75
3
1
Order By: Relevance
“…The higher average viral load among persons who reported COVID-19 symptoms than in asymptomatic persons suggests that the copy number is predictive of clinical disease. Our results of higher viral load in symptomatic than asymptomatic persons agree with findings in a recent community-based evaluating RNA levels in self-collected nasal swabs from adults and children (n=550) in Washington State 54 and a small (n=31) prospective study among patients hospitalized in China 55. However, others did not find associations between viral load and disease severity 36,56,57 Emerging data indicate that SARS-CoV-2 viral load in respiratory samples is an important driver of SARS-CoV-2 transmission 58 ; therefore, an accurate viral load measurement is an important parameter to develop mathematical models of viral spread.…”
Section: Discussionsupporting
confidence: 91%
“…The higher average viral load among persons who reported COVID-19 symptoms than in asymptomatic persons suggests that the copy number is predictive of clinical disease. Our results of higher viral load in symptomatic than asymptomatic persons agree with findings in a recent community-based evaluating RNA levels in self-collected nasal swabs from adults and children (n=550) in Washington State 54 and a small (n=31) prospective study among patients hospitalized in China 55. However, others did not find associations between viral load and disease severity 36,56,57 Emerging data indicate that SARS-CoV-2 viral load in respiratory samples is an important driver of SARS-CoV-2 transmission 58 ; therefore, an accurate viral load measurement is an important parameter to develop mathematical models of viral spread.…”
Section: Discussionsupporting
confidence: 91%
“…First, there were no differences among age groups in the median Ct values for the internal control gene ( RPP30 ) or in the time between symptom onset and sample collection ( Table 1 ). Second, there have been studies on the possible association between symptomatic infection and higher viral loads, with contrasting findings [ 6–8 ]. In this regard, it should be emphasized that in our cohort the frequency of symptomatic patients was similar across all age groups ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that both symptomatic and asymptomatic children can carry high quantities of life, replicating SARS-CoV-2, which can create a potential reservoir for SARS-CoV-2 transmission and evolution of genetic variants [ 82 ]. Unsurprisingly, studies based on the virological profiling of asymptomatic children suggested that they do have lower viral loads, as well as faster virus clearance, with no significant age-related differences [ 79 , 80 ]. Among the affected children, activated and senescent cells were higher in adults than in children, while regulatory cells were higher in children.…”
Section: Viral Load In Children and Young Peoplementioning
confidence: 99%